(untitled) (International Conference on Computers in Education, 2023)
In this study, a design framework for scientific inquiry activities for children aged 5-6 based on an AR flashcard environment is constructed, cases of scientific inquiry activities are designed according to this framework, and quasi-experimental studies are carried out. And it selects two large classes of students in a kindergarten in Xiahe County, Gansu Province of China as experimental subjects, and sets up an experimental class and a control class, with 20 students each. The research results indicate that compared with the traditional learning environment, the implementation effect of 5-6 children’s scientific inquiry activities based on an AR flashcard environment is obvious. AR technology fully mobilize children’s interest and enthusiasm for inquiry, obtain a better inquiry experience, and thus improve children’s scientific inquiry abilities.